Digital capabilities of health workers to use electronic medical records: Digital maturity self-assessment in Indonesian hospitals - Sanjaya, Guardian Yoki; Ramadhan, Devi Emrianti; Mutamakin, Agus; Sitompul, Taufiq; Sulistiyowati, Dian; Istiqlal, Haidar (International Journal of Health Literacy and Science, 2023)
Digital skills influence the successful implementation of information systems and electronic medical records (EMR) in health care facilities. The Ministry of Health measures digital maturity levels to identify gaps in improving digital transformation, including the digital skill of health workers in hospitals in 2022. The digital maturity in all hospitals in Indonesia was measured quantitatively based on the 7 components of Hospital Information Systems Maturity Model (HISMM). The low response rate was anticipated with a number of efforts such as outreach, capacity building and a circular letter from the Ministry of Health. Internal and external consistency was conducted to ensure the quality of the self-assessment. Specifically, the level of digital skills was analysed by calculating the average score of one components of digital maturity, namely Human Resources, Skills and Use of Hospital Information Systems. There are 11 parameters for assessing the level of digital literacy, perceived usefulness and encouragement to use RME in hospitals. All parameters were assessed using a 5-point scale and were analysed quantitatively. The response rate was 31.9% (973 out of 3,052 hospitals) where overall average of digital maturity level was 2.6. Hospital type A, higher accreditation status and located in Jawa-Bali has relatively high maturity level compare to others. The digital skills of health workers in hospitals are relatively high, with the majority already using the hospital information system. This was align with the perception of the ease of use and usefulness of using a hospital information system. Even though there have been several digital health champions in the hospital, health workers have not been fully involved in the process of developing information systems in hospitals and not many hospitals have utilized HIS to assess the performance of health workers. It is clearly that health workers in hospitals are capable and quite aware of the use of digital technology. However, their role needs to be increased to support the development of appropriate digital technology.